Pengembangan Sistem Point Of Sale Berbasis Web Pada Edd's Waffle Untuk Mendukung Penjualan Restaurant - Said Atharillah Alifka Alhabsyi; Fajar Pradana; Fitra A. Bachtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Culinary business is a business that is available in every region both on a small and large scale. Edd's Waffle, is a restaurant located in Pekanbaru with variant price of food and beverages that become popular among teenagers. Nowadays, Edd's Waffle uses a standard cash register, the Cash Register Sharp XE-A102 to support sales transactions. This standard cash register leaves a lot of problems in terms of sales development due to its ability to only be able to print sales receipts and provide financial reports in X-reports and Z-reports containers. To solve this problem, a point of sale system was developed to support Edd's Waffle both in terms of sales and information optimization. This point of sale system provides key features such as adding transactions, observing sales transaction history and sales progress charts, estimating revenue predictions, and identifying sales trends that contain the lists of products and best-selling product combinations. In term to optimize current data, this system utilizes 2 algorithms that contained in data mining techniques. The first algorithm is Holt Exponential Smoothing to predict Edd's Waffle's income. The selection of this algorithm is because the existing pattern of data movement is dynamic, which tends to change and is not bound by certain variables. Whereas the second algorithm is Apriori, to analyze the trends in every sold product, so that it produces information to get the combination of potential products to be paired. This system is built on web platforms. This system has been tested using unit testing and integration testing using the Whitebox method and validation testing using the Blackbox method. Beside of that, usability testing is measured using the System Usability Scale method, which the final score is 87.5 (acceptable).